2002
DOI: 10.1016/s0896-6273(02)00803-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Viewpoint on Object-Driven Activation in Dorsal and Ventral Streams

Abstract: Using fMRI, we showed that an area in the ventral temporo-occipital cortex (area vTO), which is part of the human homolog of the ventral stream of visual processing, exhibited priming for both identical and depth-rotated images of objects. This pattern of activation in area vTO corresponded to performance in a behavioral matching task. An area in the caudal part of the intraparietal sulcus (area cIPS) also showed priming, but only with identical images of objects. This dorsal-stream area treated rotated images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
153
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(175 citation statements)
references
References 40 publications
20
153
2
Order By: Relevance
“…A number of previous studies have probed the viewpoint dependence of object representations at the neural level by examining repetition suppression (RS). Some of those studies found evidence for viewpoint-invariant representations in highlevel visual cortex (Eger et al, 2004;James et al, 2002;Kourtzi et al, 2003), others found tolerance only in the left hemisphere (Vuilleumier et al, 2002) or not at all (Grill-Spector et al, 1999). While the present study cannot reconcile those reports, it introduces a new, multivariate perspective to the longstanding question of view dependence.…”
Section: Accepted M Manuscriptcontrasting
confidence: 57%
“…A number of previous studies have probed the viewpoint dependence of object representations at the neural level by examining repetition suppression (RS). Some of those studies found evidence for viewpoint-invariant representations in highlevel visual cortex (Eger et al, 2004;James et al, 2002;Kourtzi et al, 2003), others found tolerance only in the left hemisphere (Vuilleumier et al, 2002) or not at all (Grill-Spector et al, 1999). While the present study cannot reconcile those reports, it introduces a new, multivariate perspective to the longstanding question of view dependence.…”
Section: Accepted M Manuscriptcontrasting
confidence: 57%
“…The priming suppression of the BOLD response and shorter response latency occurred, however, differentially in different parts of the temporal regions, suggesting the coexistence of speaker-dependent and speaker-invariant auditory word representations. Multiple levels of object representation are not limited to the auditory modality; they have also been demonstrated in visual paradigms and in particular for view-independent and view-dependent representations within the visual What and Where pathways (James et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We make no claim that the information in the different regions is equivalent. Methods such as repetition priming Grill-Spector et al, 1999;James et al, 2002;Vuilleumier et al, 2002] or dynamically adaptive imaging [Cusack et al, 2010] may be useful to further investigate what object properties are represented in various regions, and to link the observed neural data to the statistics of the stimuli that were used in the experiment. Furthermore, although beyond the scope of this paper, it might be of interest to identify whether the information contained in the identified regions is used in behavioral performance [Williams et al, 2007].…”
Section: Conclusion and Discussionmentioning
confidence: 99%